Langerhans cell histiocytosis in an adult with oral cavity involvement: Posing a diagnostic challenge - Richa Nangalia; Rudra Prasad Chatterjee; Sanchita Kundu; Mousumi Pal (Wolters Kluwer Medknow Publications, 2019)
Langerhans cell histiocytosis (LCH) is a rare hematological disorder characterized by local or generalized, uncontrolled proliferation and infiltration of Langerhans type of histiocytic cells. It represents a spectrum of clinicopathologic disorders, ranging from a highly aggressive and frequently fatal multisystem disease to an easily cured solitary lesion of bone. Involvement of children and the younger age group is more common than the adults. Oral cavity involvement occurs early in LCH, but the initial symptoms are generally nonspecific, often causing misdiagnosis. This report describes a rare case of chronic localized LCH in an adult patient, with involvement of oral cavity. A 34-year-old male patient presented with multiple nodulo-papular, ulcerated lesions in gingiva involving both the jaws (primarily mandible) and the left buccal mucosa, in addition to regional teeth mobility. The most striking feature was that even after extraction of mobile teeth, the lesions persisted. After recording proper history, performing clinical and radiological evaluation, an incisional biopsy was performed followed by histopathology and immunohistochemistry to reach a confirmatory diagnosis of LCH, thereby implementing early and appropriate initiation of treatment.